The Kinetics of Total Phenolic Content and Monomeric Flavan-3-ols during the Roasting Process of Criollo Cocoa - Editha Fernández-Romero; Segundo G. Chavez-Quintana; Raúl Siche; Efraín M. Castro-Alayo; Fiorella P. Cardenas-Toro (MDPI AG, 2020)
Cocoa beans are the main raw material for the manufacture of chocolate and are currently gaining great importance due to their antioxidant potential attributed to the total phenolic content (TPC) and the monomeric flavan-3-ols (epicatechin and catechin). The objective of this study was to determine the degradation kinetics parameters of TPC, epicatechin, and catechin during the roasting process of Criollo cocoa for 10, 20, 30, 40, and 50 min at 90, 110, 130, 150, 170, 190, and 200 °C. The results showed a lower degradation of TPC (10.98 ± 6.04%) and epicatechin (8.05 ± 3.01%) at 130 °C and 10 min of roasting, while a total degradation of epicatechin and a 92.29 ± 0.06% degradation of TPC was obtained at 200 °C and 50 min. Reaction rate constant ( <semantics> k </semantics> ) and activation energy ( <semantics> E a </semantics> ) were 0.02−0.10 min−1 and 24.03 J/mol for TPC and 0.02−0.13 min−1 and 22.51 J/mol for epicatechin, respectively. Degradation kinetics of TPC and epicatechin showed first-order reactions, while the catechin showed patterns of formation and degradation.